Japan's Corporate Income Tax-Overview and Challenges - Dalsgaard, Thomas (IMF Working Papers; Working Paper, 2008)
The structure of Japan's corporate income tax system is broadly in line with those of other G7 countries. However, relatively high marginal and average effective tax rates prompt the question of whether adjustments should be considered to meet the objectives of promoting growth, investment and competitiveness in a revenue neutral manner. This paper discusses key issues and trade-off's related to changes in the corporate income tax system. It does not provide recommendations, but raises issues that could hopefully serve as useful inputs to the ongoing discussion and tax debate in Japan.